Interação entre desfolha e população de plantas na cultura do milho na região oeste do Paraná - Marchi, Sérgio Luiz (2008)
The corn (Zea mays L.) is considered one of the main species used in the world, once that around 150.4 millions of hectares are cultivated per year, which contribute to the production of roughly 812.2 millions tons of grains. The reduction of the photosynthetic rate after the flowering can occur due to several factors as water stress, long foggy, destruction of the leaf area (plague and illnesses) and a high population of plants. This situation needs the usage of a store, mainly from the stem to filling the grains. In this context, the current work intended to evaluate the effect of the plants population, the levels of defoliation in agronomic aspects and the yield of the hybrid corn Pioneer 30F35. An experiment was conducted on a field of Palotina PR C.Vale Experimental Field in the agricultural year of 2006/2007. It was used the delineation in blocks, at random, using a factor scheme (4 x 5), with four replications. The factors evaluated were four plants population (45.000, 55.000, 65.000 and 75.000 plants ha-1) and five levels of defoliation (without defoliation 0%, 12.5%, 25%, 37.5% and 50% of defoliation) in full female flowering (notorious stigma-style). It was found to succeed that an interaction between the plants population and the rate of defoliation to the hybrid corn studied, to the biometric variables and the productive aspects studied happened. The rate of plants remobilization was not affected by the plants population change, although, the defoliation above 25% has negatively affected this variable. The rise of the plants population resulted in plants with less diameter of stem and a rise percentage of broken plants. This enlargement of the plants population and the level of defoliation resulted in a fall of the greater part of the production components and yield of the hybrid corn Pioneer 30F35